ENFERMEDADES CRÓNICAS NO TRANSMISIBLES Y COVID-19: LA CONVERGENCIA DE DOS CRISIS GLOBALES. - Morejón Giraldoni, Alain Francisco (2020)
Epidemics of unknown emerging diseases such as COVID-19 put to the test not only the technical and human capacity of health professionals who directly care for the sick, but, and above all, that of health systems and society in general. For a proper understanding of this phenomenon, they must be approached with a general approach that integrates many elements that, otherwise, can only give a partial view of the matter. On the other hand, a situation like this, which threatens the lives of many people, creates great social tension and the need to find effective responses in the shortest possible time. COVID-19 is the most serious global crisis since World War II